DEVELOPMENT OF A MULTIPLE-CHOICE ITEM ANALYSIS APPLICATION TO ENHANCE LEARNING ASSESSMENT INSTRUMENTS - Hilyah Ashoumi; Siti Citra Aulia Aprina; Muhammad Kris Yuan Hidayatulloh; Munifah Munifah; Iskandar Tsani (Nurul Jadid University, Paiton Probolinggo, East Java, 2025)
The research aimed to ascertain the viability, receptivity of teachers to the implementation of multiple-choice item analysis and to develop a multiple-choice item analysis application in desktop form. This type of research was developed using the research and development (R&D) method. This research employs the ADDIE development model, which comprised five stages. The phases of analysis, design, development, implementation, and evaluation were employed. The results of this research indicated that the level of feasibility, based on the first media expert with a percentage value of 85%, was declared